The Pecan Truffle (Tuber lyonii): A Gourmet Truffle Native to the Southeastern United States - Arthur C. Grupe; Timothy Brenneman; Gregory Bonito; Matthew E. Smith (EDIS)
A truffle is a round, knobby, or lobed mushroom fruiting body that forms below ground. The “pecan truffle” (Tuber lyonii) is an edible truffle species, native to eastern North America. This fungus lives in a mutually beneficial relationship with the roots of some trees, including species of oak, hazelnut, and hickory trees, as well as the cultivated pecan tree. This 4-page fact sheet describes the pecan truffle, its economic and culinary significance, morphology, and phenology and distribution. Written by Arthur C. Grupe II, Timothy Brenneman, Gregory Bonito, and Matthew E. Smith, and published by the Plant Pathology Department, October 2016.